The Effect of Word Chain Game on Vocabulary Mastery: A Study at Mts Hidayatush Shibyan Cendoro Palang Tuban - salamun (JEET, Journal of English Education and Technology, 2023)
Vocabulary is one of the important aspects in teaching language included English. Vocabulary is one of the important language components that need to be taught to support learners in mastering language skill. We can use a lot of media to attract the student’s interest in learning process. One of the media is games. The use of games is very helpful for teachers to bridge the student’s motivation and learning interest. The objective of the research is to know the effectiveness of Word chain game in teaching vocabulary mastery. The research design is experimental research. The researcher apply pre-experimental one group pre-test-post-test design. The subject of the research was students’ VIII A of Mts Hidayatush Shibyan Cendoro Palang Tuban. Tehnique of data collection is test, pre-test, treatment, and pos-test. Meanwhile, tehnique of data analysis the researcher used t-test. The result of the research showed the sum score of the students in pre-test before treatment was 1935. Then, the students sum score of post-test after treatment was 2470. The researcher analyzes the result of t-test analysis to answer the research problem. The researcher gets the value of t-test analysis which 7, 77. The value of t-test analysis is consulted in t-table. From t-table shows the value of 5% is 2, 06, it mean that value 2, 06 ˂ 7, 77. So, this research showed a significant effective of Word Chain Game on Vocabulary Mastery. The result of this research, conclude that students who are taught by word chain game got higher score on their vocabulary.